Chirality control in white-light emitting 2D perovskites. Issue 28 (24th June 2020) - Trujillo-Hernández, Karla; Rodríguez-López, Germán; Espinosa-Roa, Arian; González-Roque, Jesús; Gómora-Figueroa, A. Paulina; Zhang, Weiguo; Halasyamani, P. Shiv; Jancik, Vojtech; Gembicky, Milan; Pirruccio, Giuseppe; Solis-Ibarra, Diego
Abstract : Induction of white light emission and chiroptical properties in 2D perovskites is achieved and controlled through the incorporation of chiral cations. Abstract : The increased interest in white solid-state lighting devices addresses the urgent challenge to develop semiconductors with broad band emission. In recent years, low dimensional hybrid organic/inorganic lead perovskites have shown great potential as single white-light emitters. Herein, we show that it is possible to control the chirality of lead bromide perovskites by incorporating enantiopure ( R or S ) or racemic ( RS ) β-methylphenethylammonium. The incorporation of such cations allows us to control the chirality of the resulting materials and yields the first examples of 2D chiral perovskites that emit white light. Furthermore, we demonstrate that these materials exhibit second harmonic generation. Our results demonstrate the potential of this kind of materials for chiroptical applications and non-linear optics.